2004
DOI: 10.1007/s10350-004-0550-y
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Hemorrhoidectomy With Local Anesthesia can be Performed Safely and Cost-Efficiently

Abstract: Administration of general, spinal, or epidural anesthesia for the procedure for prolapsing hemorrhoids is well described. This study suggests that the use of local anesthesia supplemented with conscious sedation for the procedure for prolapsing hemorrhoids yields results equivalent to those achieved with general or regional anesthesia without the attendant risks and additional costs. This study also suggests that the presence of muscle fibers in the pathologic specimen does not seem to lead to increased pain o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 55 publications
2
33
0
4
Order By: Relevance
“…Cases of urosepsis were also seen concomitantly in a small number of patients with urinary retention. 22 Early fecal urgency was reported and reported rates ranged from 0 to 25%, with a median occurrence of 8.28%. 5 Early constipation was also reported in 5 patients (0.03%) and in 2 cases, a fecaloma resulted (0.014%).…”
Section: -16 Documented Complications Of Hemorrhoidopexy Porrettmentioning
confidence: 99%
“…Cases of urosepsis were also seen concomitantly in a small number of patients with urinary retention. 22 Early fecal urgency was reported and reported rates ranged from 0 to 25%, with a median occurrence of 8.28%. 5 Early constipation was also reported in 5 patients (0.03%) and in 2 cases, a fecaloma resulted (0.014%).…”
Section: -16 Documented Complications Of Hemorrhoidopexy Porrettmentioning
confidence: 99%
“…KHALIL et al (12) have found that postoperative resting and squeeze pressures were reduced by stapled method at 3 months but normal pressure profile was observed at 6-month evaluation. The frequent presence of muscle fibers in the pathologic specimen does not seem to lead to impaired continence, as pointed out by ESSER et al (6) .…”
Section: Postoperative Incontinencementioning
confidence: 56%
“…This feeling is often uncomfortable; therefore, medication needs to be administered, to sedate the patients. Infiltration can be performed in combination with sedation, 17 or with general anesthesia as in this study. Another study has also combined these methods.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ropivacaine causes vasoconstriction, which limits its blood absorption. 19 Alternatively, short-acting lidocaine 17 or bupivacaine 12 can also be used.…”
Section: Discussionmentioning
confidence: 99%